Geometria

Solo disponible en BuenasTareas
  • Páginas : 5 (1177 palabras )
  • Descarga(s) : 0
  • Publicado : 21 de agosto de 2012
Leer documento completo
Vista previa del texto
0057695601
0057695601

ALUMNO:VARGAS MARTINEZ DANIEL DE JESUS
PROFESOR:DAVID RIVERA
CORREO ELECTRONICO:slipknot_soat@hotmail.com
GRADO:2 SEMESTRE
GRUPO:AV-MAU
ALUMNO:VARGAS MARTINEZ DANIEL DE JESUS
PROFESOR:DAVID RIVERA
CORREO ELECTRONICO:slipknot_soat@hotmail.com
GRADO:2 SEMESTRE
GRUPO:AV-MAU

7) Sen x + cos x/sen x =1-1/tan x
Sen x + cos x/senx=1+1/tan x(=) sen x +cos x/sen x=1+ cot x
Sen x + cos x/sen x = 1+1/tan x (=) sen x +cos x/sen x =1+cos x /sen y
Sen x + cos x/sen x=1+1/tan x (=)sen+cos x / sen x = sen + cos x /sen x
8)cos x/cot x=sen x
Sen/tan = sen/tan=cot=1/tan
1/tan= sen.tan/tan= sen=sen
9) sen x/cos x +cos/sec=1
Cosc=1/sen x sec=1/cos x
Sen/1/1/sen+cos/1/1cos=1
Sen2 /1+cos2 /1=1=sen2 x+cos2 x =1=1
10)tan x/sen x =sec x
Tan g /1=sen/cossen/cos/1/sen =sen.sec/cos=cos=sec x
1/sec=sec=sec
11)sec y/tan y+cot y=sen y
Sec=cos tan=sen/cos cot=cos/sen
1/cos / sen/cos cos/sen=1/cos/sen.cos/cos.sen 1/cos/1/cos.sen=cos.sen/cos=sen
Sen=sen
12)csc x/cot x =sec
Cos c=1/sen cot cos/sen=1/sen/cos/sen=sen/sen.cos=cos
Cos=1sec= sec=sec
13)1-sen x/cos x=cos x/1+sen x
Cos x2/cos x=cos x
Cos x/(-)1-sen x=cos x/1+sen x
Cos x/1+senx=cos x/1+sen x
14)sen4z=1-cos2z/csc2z
1-cos2z/csc2z=sen4z=(sen 2/2)(sen2z)
1-cos2z/csc2z=1/sen2z/1/sen2=sen2csc2z=1-cos2z/csc2z
1-cos2z/csc2z=1-cos2z/ csc2z
15)sec x (1-sen2 x)=cos x
1/cos x(-cos2x) =cosx
1/cos x(-1/cos2x)=cosx
Cos x=cos x
16)tan z.cos z.csc z=1
Seno/cos 1/cos z 1/csc
(seno/cos) (1/cos 1/csc)=sen x.csc x.=1
1=1
17)sen x.sec x=tang x
Sen=cos x tan x.1/cosCos.tan.1/cos=tang
Tang=tang
18) tang x-sen x/sen3x=sec x/1+cos x
Tan=1cot+sen x=cos/cot=cot/cot.cos/1+cos x
Cos=1/sec=sec x/1+cos x=sex x/I +cos x
19)1/sec y + tan y=sec y-tan y
1/sec y +tang y=1/sec x+ 1/tan
1/sec y+tan y=1/sec y +tan y
20)csc x/tan x+cot x=cos x
Csc=1/sen x tan x=sen x/cos c
1/sen x/sen x/cos x+cos/sen=1/sen x/sen2cos2 x/cos x sen x=1/sen x/1/cos x sen x
Cosx senx/sen x=cos x=cos x
25)cos2x=(1+sen x)(1-sen x)
=(a+b)(a-b)
=1-sen x=cos2x
cos2x =cos2x
26)(1-sen2x)(1+tan2x)=1
1-sen=cos 1+tan x =sec
Cos+sec=1/cos
Cos-1/cos=1
1=1
27)sen x+cos x/sen x-cos x=sec x+csc x/sec x –csc
Sen=1/csc cos=1/sec
1/sec+1/csc/1/sen+1/csc=
Sec x+csc x/sec x –csc x= Sec x+csc x/sec x –csc x
28)sen2x.cos2x+cos x=1-1/csc2x
Sen2+cos=1 sen2=1-cos2
1 x 1-sen2=1-1/csc2 y=1-1/csc2 y
29)tan x+tan y=tan x tan y(cot x+cot y)
=tan y tan y(cot=cos/sen)
=tan y tan y(cos.sen/cos.sen)
tan x tan y =tan x tan y
30)2 sen2x+cos2x=1+sen2x
Sen=cos/cot x cos2x=
Cos.cot+cos2x/cot.cos=1+sen2x
Cos2x=1+sen2x
1+sen2x=1+sen2x
32)1+tan2x=sec3x.cos x
1+tan4x=sec2
(sec2)(sec)=
Sen3+1/cos
Sec3x.cos x= Sec3x.cos x
33)tan2x.cot2x=sen2x+cos2x
Tan=1/cot cot+cos/sen1/cot+cos/sen= sen+sen/cos+cos
Sen2x+cos2x= Sen2x+cos2x
34)1+2 sen x cos x=sen x cos x(1+cot x)(1+tan x)
=sen x cos x(csc x)(sec2x)
=(1/sen)(1/cos)
1+2sen x cos x=1+2sen x cos x
35)1/1+sen y+1/1-sen y=2 sec2y
1/cos2+1/cos2=2sec2y
1/1/sec+1/1/sec=2 sec2y
2 sec2y=2 sec2y
36)2tan x +1=cos x +2 sen x/cos x
=cos x+sen x=1=
=1=sen=cos/cot 1/cos cot=1/tan
2 tan x+1=2 tan x+1
37)3 senx cosx=3 sen2 x cot x
3 sen x cos x =1 =3sen x cot x =1
1=1
39)2 tan+cos x=cos2x+2 sen x/cos x
Tan=sen+cos x=cos2x+2sen x/cos x
Sen x/cos x/cos x=cos2x+2sen x/cos x
Cos2x+2 sen x/cos x= Cos2x+2 sen x/cos x
41)sen x sec x cot y=1
Sen=cos/cot csc=1/cos 1/cot=1
Cos 1 1/cot.cos.1=1
1=1
45)cot2 x (1+tan2 x)csc2x
Tan(sec2x)
Tan=(tan x.csc x)=csc2x
1.tan.csc/tan
Csc2 x=csc2x
48)2 sen2z-1=(sen4z-cos4z)
=sen2z-(1-sen2z)
Sen2z-1+sen4z
2 sen2z-1=2 sen2z-1
50)1/1+tan2y-1/1+tan2x=sen2x- sen2y
1/sec-1/sec=sen2x-sen2y
1/tan.csc y-1/tan.csc x=sen2x. sen2y
Tan x.csc x-tan y .csc y= Tan x.csc x-tan y .csc y

52)tan x(cos2x-sen2x)/1-tan2x=sen3x+cos3x/sen x +cos x
Tan=1/cot cot=cos/sen(cos2x-sen2x)/cos2/sen21=
Sen3x+cos3x/sen x+cos x=sen3x+cos3x/sen x+cos x
53)tan4x-sec4x=1-2...
tracking img